Contextos funerários da tradição polícroma da Amazônia na região do Lago Tefé, Médio Solimões, Amazonas - Marinho, Karen Lorena Freire (2022)
The Lake Tefé region has great potential for archaeological studies, although since the 1960s the potential of this region has already been demonstrated, only over the last few years has local research been resumed, as can be seen by the fieldworks carried out along Lake Tefé like Jaqueline Belletti's Master's degree and for the excavations of the Tauary site in 2018 and Ponta da Castanha site in 2019. During the excavations of the Tauary site, a set of 9 funerary urns was evidenced, which have characteristics of ceramics affiliated with the Amazonian Polychrome Tradition (APT), some with anthropomorphic decorations and others with geometric motifs. The reports of occurrences of vases found buried and used for burials are quite recurrent in various parts of the Amazon region, from the 19th century onwards. However, neither the contexts nor the funerary practices have been extensively studied. The present work, therefore, aims to study the funerary context of the urns associated with the Tefé Phase of APT, excavated at the Tauary site, in 2018. For this, the methodology used in this research consists of bibliographic research, excavation of urns and laboratory analysis of the remains found inside them. From the opening and excavation of five of the nine urns, it was possible to verify that although the urns were all buried in a single pit and event, they presenteddifferent stages of conservation, both inside and outside of each one of them; it was noted that in one of the urns there was a large amount of bone material, the bones were all burned, in addition to the presence of a single individual inside. In this way, the intention of this research is to contribute to the knowledge of the regional history of the middle Solimões River and the ways of life of the ancient populations that lived around Lake Tefé, since funerary practices are very important for societies.